Deposit Insurance : Obtaining the Benefits and Avoiding the Pitfalls - Garcia, G. (Washington, D.C. : International Monetary Fund, 1996)
The paper contrasts deposit protection with other forms of insurance, examines why goods and services of all kinds receive warranties and guarantees, and explores the particular characteristics of deposits and banks that merit deposit insurance. It examines a variety of reasons why countries choose to adopt systems of deposit insurance, the pitfalls that can arise from poorly designed schemes, and the features of a scheme that successfully avoids these pitfalls.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet